Hypogammaglobulinaemia in low grade B cell tumours; significance and therapy. - Chapel, H; Griffiths, H; Brennan, V; Bunch, C; Lea, J; Lee, M (Informa Healthcare, 1991)
Bacterial infection is an important cause of morbidity and mortality in patients with B-cell tumors; this is related to their secondary hypogammaglobulinaemia. Two studies of intravenous replacement therapy [IVIg] have been performed in such patients: a crossover study over two years and a randomised, multicentre study over one year. Both involved infusions of IVIg [400 mg/Kg] or an equivalent volume of saline every three weeks for one year. In both studies, serious bacterial infections were considerably reduced by IVIg. Viral and fungal infections were uncommon. In the crossover study bacterial infections were more frequent in periods in which patients serum IgG levels were below the normal range [less than 6.4 g/l]. The sites of bacterial infection were similar in these studies to those in previously published reports, namely respiratory tract, skin, urinary tract and blood. There were a few mild adverse reactions which were related to the rate of infusion, but no serious toxic effects. Haematological parameters were not significantly changed by IVIg at this dose and disease progression did not appear to be changed.